Can the Response to Iron Therapy Be Predicted in Anemic Nondialysis Patients with Chronic Kidney Disease? - Stancu, Simona (American Society of Nephrology, 2010)
Background and objectives: Anemia is iron responsive in 30 to 50% of nondialysis patients with chronic kidney disease (CKD), but the utility of bone marrow iron stores and peripheral iron indices to predict the erythropoietic response is not settled. We investigated the accuracy of peripheral and central iron indices to predict the response to intravenous iron in nondialysis patients with CKD and anemia. Design, setting, participants, & measurements: A diagnostic study was conducted on 100 nondialysis patients who had CKD and anemia and were erythropoiesis-stimulating agent and iron naive. Bone marrow iron stores were evaluated by aspiration. Hemoglobin, transferrin saturation index (TSAT), and ferritin were measured at baseline and 1 month after 1000 mg of intravenous iron sucrose. Posttest predictive values for the erythropoietic response (≥1-g/dl increase in hemoglobin) of peripheral and central iron indices were calculated. Results: The erythropoietic response was noted in a higher proportion in bone marrow iron-deplete than in iron-replete patients (63 versus 30%). Peripheral iron indices had a moderate accuracy in predicting response. The positive (PPV) and negative predictive values (NPV) were 76 and 72% for a TSAT of 15% and 74 and 70% for a ferritin of 75 ng/ml, respectively. In the final logistic regression model, including TSAT and ferritin, the chances of a positive response increased by 7% for each 1% decrease in TSAT. Conclusions: Because an erythropoietic response is seen in half of patients and even one third of those with iron-replete stores responded whereas peripheral indices had only a moderate utility in predicting response, the therapeutic trial to intravenous iron seems to be a useful tool in the management of anemia in nondialysis patients with CKD.